Gender-affirming hormones and surgery in transgender children and adolescents. Issue 6 (June 2019) - Mahfouda, Simone; Moore, Julia K; Siafarikas, Aris; Hewitt, Timothy; Ganti, Uma; Lin, Ashleigh; Zepf, Florian Daniel
Summary: The Endocrine Society Clinical Practice Guidelines on the treatment of gender incongruent people recommend the use of gender-affirming cross-sex hormone (CSH) interventions in transgender children and adolescents who request this treatment, who have undergone psychiatric assessment, and have maintained a persistent transgender identity. The intervention can help to affirm gender identity by inducing masculine or feminine physical characteristics that are congruent with an individual's gender expression, while aiming to improve mental health and quality-of-life outcomes. Some transgender individuals might also wish to access gender-affirming surgeries during adolescence; however, research to inform best clinical practice for surgeons and other medical professionals is scarce. This Review explores the available published evidence on gender-affirming CSH and surgical interventions in transgender children and adolescents, amalgamating findings on mental health outcomes, cognitive and physical effects, side-effects, and safety variables. The small amount of available data suggest that when clearly indicated in accordance with international guidelines, gender-affirming CSHs and chest wall masculinisation in transgender males are associated with improvements in mental health and quality of life. Evidence regarding surgical vaginoplasty in transgender females younger than age 18 years remains extremely scarce and conclusions cannot yet be drawn regarding its risks and benefits in this age group. Further research on an international scale is urgently warranted to clarify long-term outcomes on psychological functioning and safety.